2014
DOI: 10.1089/vbz.2013.1362
|View full text |Cite
|
Sign up to set email alerts
|

A Surveillance Program on Canine Leishmaniasis in the Public Kennels of Emilia-Romagna Region, Northern Italy

Abstract: Since 2007, a canine leishmaniasis (CanL) surveillance program has been carried out in public kennels of the Emilia-Romagna region with the aim of providing health guarantees for dog adoptions. According to this program, monitoring activities were performed to verify the presence of sandflies and infected dogs, and a specific CanL risk class was assigned to each kennel, resulting in different control approaches (entomological and/or serological monitoring, clinical surveillance, therapeutic treatment of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In this study, the seroprevalence of L. infantum (2.5%) was found to be higher in older animals and overall similar to that recently observed in kennels from other areas of central and northern Italy, showing low/medium infection levels, from 2.8% to 17.9% [ 3 , 39 , 40 ]. L. infantum is a protozoan species responsible for a very important zoonotic disease representing a serious veterinary and public health problem.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the seroprevalence of L. infantum (2.5%) was found to be higher in older animals and overall similar to that recently observed in kennels from other areas of central and northern Italy, showing low/medium infection levels, from 2.8% to 17.9% [ 3 , 39 , 40 ]. L. infantum is a protozoan species responsible for a very important zoonotic disease representing a serious veterinary and public health problem.…”
Section: Discussionsupporting
confidence: 88%
“…Among dog parasites of major zoonotic concern, Leishmania infantum is an important vector-borne parasite of the dog, which is considered the main domestic reservoir host for human infections [ 34 ]. Canine leishmaniosis is endemic in Italy and in other countries of the Mediterranean basin, with a widely variable prevalence [ 15 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sand flies are mainly distributed in the hilly areas of the region, including the neighbouring area between Modena and Bologna provinces. P. perfiliewi represents the most abundant species [19] and it is considered a less efficient vector of L. infantum [17] in comparison to P. perniciosus . However, Baldelli et al [20] reported a canine leishmaniasis focus sustained by P. perfiliewi and its role in the VL transmission also cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to dogs, recognized as primary reservoir hosts of zoonotic VL, any important changes in the canine leishmaniasis epidemiology were observed. Results of a multiyear surveillance program carried out in public kennels of Emilia-Romagna showed an increase in canine leishmaniasis seroprevalence from 2010 (1%) to 2012 (2.4%) [19]. Afterwards a slight decrease was observed [21], with prevalence values lower than those observed in traditionally endemic regions of central and southern Italy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Available field data suggest that these insects are spreading northwards in Europe (northern Italy, Austria, Germany and Hungary) and their densities are increasing in some newly colonised areas . Owing to the wide distribution of susceptible dogs and the high host-vector contact rates, the main limitation to CanL spread is probably represented by the vectors (Santi et al, 2014). This reinforces the need for improving our knowledge of the vectorial competence of some sandfly species and of the distribution and abundance of known vectors.…”
Section: Discussionmentioning
confidence: 98%